Non-standard monetary policy measures and monetary developments - Domenico Giannone; Michele Lenza; Huw Pill; Lucrezia Reichlin (European Central Bank (ECB), 2011)
Standard accounts of the Great Depression attribute an important causal role to monetary policy errors in accounting for the catastrophic collapse in economic activity observed in the early 1930s. While views vary on the relative importance of money versus credit contraction in the propagation of this policy error to the wider economy and ultimately price developments, a broad consensus exists in the economics profession around the view that the collapse in financial intermediation was a crucial intermediary step. What lessons have monetary policy makers taken from this episode? And how have they informed the conduct of monetary policy by leading central banks in recent times? This paper sets out to address these questions, in the context of the financial crisis of 2008-09 and with application to the euro area. It concludes that the Eurosystem's non-standard monetary policy measures have supported monetary policy transmission and avoided the calamity of the 1930s.
Keywords: E5; E4; E32; 330; Great Recession; monetary policy shocks; money and credit; Non-standard monetary policy